PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI NON FINANSIALTERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DI PUSKESMAS KECAMATAN BATANG CENAKU INDRAGIRI HULU - , Ahmad Rifqi, Teguh Prayitno , Dewita Suryati Ningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of the work environment and non-financial compensation on the performance of Puskesmas employees through employee job satisfaction in Batang Cenaku District, Indragiri Hulu Regency. The population in this study were 49 employees at the Puskesmas. Primary data in this study were collected using a questionnaire as an instrument to prove the results of the study. To test the hypothesis in this study, Structural Equation Modeling - Partial Least Square (SEM-PLS) was used with the help of the SmartPLS 3.0 program. The sampling technique was carried out using the Saturated Sampling Method (Census) and 49 PNS Employees (Civil Servants) were selected as samples. The results showed that: 1) There is a positive but not significant influence between the Work Environment on the Job Satisfaction of Health Center Staff in Batang Cenaku District, Indragiri Hulu Regency, 2) There is a positive and significant influence between Non-Financial Compensation on the Job Satisfaction of the managers of Batang Cenaku District, Regency Indragiri Hulu, 3) There is a positive and significant influence between the Work Environment on the performance of Puskesmas employees in Batang Cenaku District, Indragiri Hulu Regency, 4) There is a positive and significant influence between Non-Financial Compensation on the performance of Puskesmas employees in Batang Cenaku District, Indragiri Hulu Regency, 5) There is a positive and significant influence between satisfaction on the performance of PUSKESMAS managers in Batang Cenaku District, Indragiri Hulu Regency, 6) There is a positive but not significant influence between the Work Environment on performance through employee job satisfaction as i intervening variables in Batang Cenaku District, Indragiri Hulu Regency, 7) There is a positive and significant influence between Non-Financial Compensation on performance through Employee Job Satisfaction as an intervening variable in Batang Cenaku District, Indragiri Hulu Regency. Keywords: Work Environment, Non-Financial Compensation, Performance, Satisfaction